2018
DOI: 10.4103/ijc.ijc_428_17
|View full text |Cite
|
Sign up to set email alerts
|

Locally advanced cervical cancer: A study of 5-year outcomes

Abstract: Five-year DFS of 62% and 45% of Stage II and III patients treated under routine care represents comparable stage-matched results to the rest of the world, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 9 publications
4
30
1
4
Order By: Relevance
“…The current therapy for CC mainly includes surgical treatment, cytotoxic chemotherapy, and radiotherapy. Despite advances in these traditional and newly emerging therapeutic modalities for CC, the 5-year disease-free survival (DFS) rates for advanced staged CC patients are only 45% [6]. Hence, it is crucial to investigate and identify the molecular aberrations in CC so as to develop more effective therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The current therapy for CC mainly includes surgical treatment, cytotoxic chemotherapy, and radiotherapy. Despite advances in these traditional and newly emerging therapeutic modalities for CC, the 5-year disease-free survival (DFS) rates for advanced staged CC patients are only 45% [6]. Hence, it is crucial to investigate and identify the molecular aberrations in CC so as to develop more effective therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal chemoradiation and brachytherapy (BT) in locally advanced cervical cancer (LACC) are associated with 5-year survival rates of 75% and 55% in those with stage IB2 to IIB and IIIB disease, respectively, in clinical trials and tertiary care centers in India. 5-8 Therefore, the National Cancer Grid of India and Indian Council of Medical Research recommend that chemoradiation and BT be the standard of care for LACC. 9,10…”
Section: Introductionmentioning
confidence: 99%
“…Chopra et al . observed that the patients aged over 70 years had a significantly poor DFS at 5 years; however, did not have any effect on survival [ 30 ]. In our study, we have found better survival rates in patients older than 62 years.…”
Section: Discussionmentioning
confidence: 99%